PENGARUH UPAH MINIMUM PROVINSI DAN TINGKAT PENDIKAN TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI MALUKU UTARA TAHUN 2009-2023 - Benidita Lake; Amran T. Naukoko; Wensy Frangky Israel Rompas (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The relatively high unemployment rate in North Maluku Province indicates challenges in labor absorption, although the government has made efforts to implement minimum wage policies and increase access to education. This study aims to analyze the effect of the Provincial Minimum Wage (UMP) and education level on labor absorption in North Maluku Province during the period 2009–2023. The data used in this study are secondary data obtained from data from the Central Statistics Agency. This study is a type of quantitative descriptive research with a multiple linear regression  analysis model and the software used to conduct the analysis is Eviews 12. The results of the analysis show that the provincial minimum wage variable has a positive and significant effect on labor absorption in North Maluku, education level has a positive and insignificant effect on labor absorption in North Maluku. Simultaneously, the provincial  minimum wage and education level have a positive effect on labor absorption in North Maluku.